Clima organizacional y satisfacción laboral de los empleados en la Municipalidad Distrital de Pacasmayo: 2021 - Jiménez Segura, Gandy Shiomara (2022)
This thesis was carried out with the purpose of analyzing the influence of the organizational climate on the job satisfaction of employees in the district municipality of Pacasmayo: 2021. The type of applied research has been considered, based on a descriptive design, and the sample consisted of 92 employees of the District Municipality of Pacasmayo, with whom we worked applying the methods and techniques of quantitative research (statistical method and as technique to the virtual survey) and qualitative research (inductive - deductive method) and as a technique the virtual interview. From the results obtained, it has been possible to determine that the poor organizational climate, the lack of rewards and work incentives influence the job satisfaction of employees in the district municipality of Pacasmayo. Consequently, it is important that the District Municipality of Pacasmayo know its organizational climate and the job satisfaction of its employees, which makes it possible to analyze the results using this research as a guide. Therefore, the results conclude that for there to be optimal job satisfaction, it is necessary for the organization to have an adequate organizational climate. Finally, we consider that the organization must implement training programs to implement a motivation plan, promote transformational leadership and work as a team to improve the level of production and productivity of the organization. This thesis is subdivided into: I. Introduction: Problematic reality, background, theoretical bases and conceptual framework; II. Methodology; III. Results; IV. Discussion V. Conclusions; VI. Bibliographic references and Annexes.